DRAMATURGIA RADIOWA WEDŁUG JERZEGO SZANIAWSKIEGO - Motyka, Urszula (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Jerzy Szaniawski was undoubtedly a great radio playwright. His dramas, such as Adwokat i róże / The Attorney and Roses/, Ptak /The Bird/, Żeglarz /The Sailor/, Zegarek /The Watch/, Służbista /The Official, teem with elements that are essential for a radio play. In his works, Szaniawski aimed at full generalisation of the theme, place and time. He pictured the souls of his characters and clearly portrayed their psychological delineation. Szaniawski started his cooperation with radio in 1935 with his play The Watch. Due to his exceptional artistic sensibility he was able to integrate into his works the elements which are crucial for a radio play. These are, primarily, audio elements, dialogues and narratives that are present in all his dramas, retrospections, which appear only in three plays: The Attorney and Roses, The Official and The Watch, as well as reticence and understatements employed in Attorney and Roses and The Watch. All of the above mentioned elements aim at stimulating the listeners’ sense of hearing and consequently creating the represented world in their imagination.